The Sensitivity of Long-Term Interest Rates to Economic News: Evidence and Implications for Macroeconomic Models - Gürkaynak, Refet S; Sack, Brian; Swanson, Eric (American Economic Review, 2005)
The Sensitivity of Long-Term Interest Rates to Economic News: Evidence and Implications for Macroeconomic Models by Refet S. Gürkaynak, Brian Sack and Eric Swanson. Published in volume 95, issue 1, pages 425-436 of American Economic Review, March 2005